Analysis of Dye-Penetrant Test, Tensile Test, and Bending Test Results of Shielded Metal Arc Welding (SMAW) on Carbon Steel ASTM A106 Grade B Pipes in 6G Welding Position at PPSDM Migas Cepu - Setiawan, Agris; Gracella, Gracella; Hoka Padmanaba, Faqih; Alfianur Hakim, Haidar Alfianur Hakim (Journal of Metallurgical Engineering and Processing Technology, 2024)
The weld quality its significantly depends on the mechanical characteristics of weld joint, the welding process, parameters weld process and also material selection. Insufficient parameter values and welding method can lead to welding defects and distortion that adversely affect mechanical properties. Consequently, carefully selecting appropriate weld method at an optimal level becomes crucial to mitigate defects, enhance productivity, and achieve desirable mechanical attributes in shielded metal arc welding (SMAW). PPSDM Migas has special facilities for conducting welding workshops or training and for equipment inspection or testing in the metallurgy laboratory. One of the inspected items is the welding used to join pipes. In this study, the inspected pipe is Carbon Steel ASTM A106 Grade B, welded using SMAW in the 6G position from the PPSDM Migas Cepu Refinery Unit area. The inspection methods used in this study are the Dye-Penetrant Test, Tensile Test, and Bending Test to identify welding defects and material strength. The tests conducted refer to ASME Section IX. Based on the DyePenetrant Test results on the Carbon Steel ASTM A106 pipe joint, five rounded defects were found on the weld surface, still within the acceptance criteria of ASME Section IX, thus the pipe is declared accepted. According to the Tensile Test results, spesimens 1 and 2 broke in the weld area but met the ASME Section IX criteria with tensile strengths of 464.098 MPa and 713.597 MPa, respectively, both exceeding 415 MPa, which is the tensile strength of ASTM A106 carbon steel. However, the Bending Test results showed open defects up to 3 mm, causing the pipe joint to be declared declined.